Processes of covariational reasoning during the cognitive integration of mathematics and physics concepts in the interpretation of hydraulic flow - Castañeda Ovalle, Alfonso; García Rodríguez, Martha Leticia (IE Revista de Investigación Educativa de la REDIECH, 2023)
The objective of this study was to analyze, through the theoretical approach of cognitive integration, the process of covariational reasoning on a group of students when they interpret the concept of hydraulic flow. Five activities were designed and applied in virtual mode, two of which that included the use of dynamic simulators and digital workbooks are reported in this work. The answers, graphics and comments of the students were analyzed with theoretical elements of cognitive integration, of the variational and covariational reasoning, and of hydraulic flow. The way in which students make sense of their mathematical ideas was identified when they analyze the physical phenomenon of filling one cylinder; to observe how they mobilize their variational and covariational reasoning to support their understanding of the variables related with hydraulic flow and change in height and volume variables of the liquid. The analysis of the evidence allowed to know about the processes of cognitive integration between elements of mathematics and physics, and to recognize behaviors related with different levels of variational or covariational reasoning exhibited by the students.